Usable security: A browser’s security warnings assessment - Boniface Emang, Devinna Win; Zaaba, Zarul Fitri; Hussain, Azham (Science and Engineering Research Support Society, 2020)
Security warning is a form of message of alerting. It specifies the functions to notify, to warn and to advice users about the consequence or any possible menaces by allowing random applications to run on the computer system. However, the majority of computer user tends to ignore security warnings that convey excessive technical messages which are difficult for user to understand and lead to lack of motivation for decision making. A survey utilised 250 participants had been conducted to address end-user’s comprehension about the warnings based on their browser’s preference. The results revealed that most users preferred to use Google Chrome and Mozilla Firefox as compared to Safari and Internet Explorer. It can be noted that users experienced significant challenges to comprehend the signal icons and technical jargon based on the presented warnings. There is a corresponding need to design a usable security warning that able to ease end-users security decision.